The Function of FK506-Binding Protein 13 in Protein Quality Control Protects Plasma Cells from Endoplasmic Reticulum Stress-Associated Apoptosis - Jeong, Mini; Jang, Eunkyeong; Choi, Suk San; Ji, Changhoon; Lee, Kyungho; Youn, Jeehee (Frontiers in Immunology, 2017)
Plasma cells (PCs) are exposed to intense endoplasmic reticulum (ER) stress imposed by enormous rates of immunoglobulin (Ig) synthesis and secretion. Therefore, protein homeostasis is crucial for the survival of PCs, but its molecular mechanism remains largely unknown. Here, we found marked overexpression of FK506-binding protein 13 (FKBP13) in long-lived PCs from autoimmune mice and investigated its function using a plasmacytoma cell line secreting IgA. FKBP13 expression was induced largely in the lumen of ER in response to treatment with an ER stressor tunicamycin or overexpression of an adaptive unfolded protein response (UPR) protein X-box binding protein 1 (XBP1). Silencing of FKBP13 expression led to induction of molecules involved in the terminal UPR and ER stress-associated apoptosis. FKBP13 interacted with Ig, facilitated its ubiquitination, and lowered the extent of ER stress. FKBP13 overexpression caused a significant reduction in secreted IgA in plasmacytoma cells, and FKBP13 knockdown exerted an opposite effect. Rapamycin interfered with the interaction between FKBP13 and IgA and enhanced the amount of secreted IgA. Importantly, the level of FKBP13 was inversely correlated with the amount of secreted antibody in long-lived PCs from autoimmune mice. These results suggest that FKBP13 is a marker of long-lived PCs and a component of XBP1-dependent ER protein homeostasis. FKBP13 is likely to act as a molecular chaperone that delivers misfolded ER clients, including Ig, to ER-associated degradation, so reducing proteotoxic stress on the PC. Our data reveal a novel cytoprotective role for FKBP13 in long-lived PCs occurring at the expense of antibody production.